2020
DOI: 10.1016/j.jmbbm.2020.103860
|View full text |Cite
|
Sign up to set email alerts
|

Flow dynamics of vitreous humour during saccadic eye movements

Abstract: In this work, we reveal the flow dynamics of Vitreous Humour (VH) gel and liquid phases during saccadic movements of the eye, considering the biofluids viscoelastic character as well as realistic eye chamber geometry and taking into account the saccade profile. We quantify the differences in the flow dynamics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The absence of the vitreous gel after vitrectomy is believed to enhance the ow of vitreous humor into the anterior chamber during eye movements. Silva and associates 13 reported that computational uid dynamics of vitreous humor during saccadic eye movements was different for the gel phase in the vitreous cavity than that with the liquid phase because the inertial effects were more signi cant with the liquid vitreous. In contrast, the shear stress produced by the gel phase of vitreous humor more than twice that of liquid phase.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The absence of the vitreous gel after vitrectomy is believed to enhance the ow of vitreous humor into the anterior chamber during eye movements. Silva and associates 13 reported that computational uid dynamics of vitreous humor during saccadic eye movements was different for the gel phase in the vitreous cavity than that with the liquid phase because the inertial effects were more signi cant with the liquid vitreous. In contrast, the shear stress produced by the gel phase of vitreous humor more than twice that of liquid phase.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the shear stress produced by the gel phase of vitreous humor more than twice that of liquid phase. 13 After an intrascleral xation of an IOL without a lens capsular support, the height of the temporal sector of the iris increased, and the nasal sector decreased immediately after the eye moved from a temporal gaze to the primary position. The aqueous humor is more susceptible to the inertia moments than the vitreous humor during eye movements because the aqueous humor is located further from the center of the eye.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, research has been reported [15,17,[22][23][24][25][26][27] to study the effects of saccades on the convective-diffusive behaviour of a drug via IVT delivery. Saccadic eye movements are ballistic movements produced by both eyes, and help orient the line of sight when fixating on an object [28,29]. The characteristics of saccades include a very high initial acceleration, a weaker deceleration, and a peak angular velocity associated with the saccadic amplitude [24].…”
Section: Introductionmentioning
confidence: 99%